A Computational Modeling of the Influence of Different Oxy-fuel Combustion Environment on Combustion Characteristics and Particles Temporal History. Issue 6 (26th April 2021) - Yadav, Sujeet; Mondal, S.S.
ABSTRACT: In the present article, CFD simulation of various oxy-fuel combustion cases has been performed to find out the influences of oxy-fuel combustion environment on temperature distribution, char consumption, radiative properties and temporal variation of particle phase variables such as particle temperature, volatile and char mass fraction. The oxy-fuel combustion cases are obtained by varying O2 and CO2 concentrations while keeping the total volume flow rate constant. Four oxy-fuel cases are considered in the present work having oxygen concentration 21%, 25%, 30%, and 35%. The present article also investigates the influence of char gasification reactions on temperature distribution, species concentration and temporal profile of particle char mass fraction. The predicted temperature distribution and radiative properties under oxy-fuel cases are compared with the corresponding values obtained under air-fired combustion as for retrofit existing power plants comparable values are desirable. The oxy-30 case having 30% oxygen has almost identical temperature and radiative profiles. With an increase in oxygen concentration in oxy-fuel cases leads to an increased peak temperature and surface incident radiation due to the rise in local stoichiometry, which results in enhanced reaction kinetics and burning rate. The peak temperature obtained in oxy-25, oxy-30 and oxy-35 cases is around 10%, 18%, and 24% higher than the oxy-21 case. Reduced char burnout time is obtained due to the presence of gasification reactions.